Fifth Five Year Plan Draft Annual Plan 1977-78 Vol. II Uttar Pradesh - Planning Commission (Planning Commission, 1976)
Industrialisation has a vital role in providing employment, raising standard of living and utilisation of resources. In Uttar Pradesh it is imperative that the pace of industrialisation should be accelerated as the contribution of industries to the State income so far accounts for only 11 per cent. The State Government has adopted a policy of increasing industrial growth by creating favourable industrial climate and developing infra-structural facilities in various parts of the State, which may lead to an additional advantage of syphoning the surplus labour' from agriculture to industrial pursuits.
Uttar Pradesh Planning Department